Does nudging intentions translate into action? Why nudging pledges to charities does not result in increased donations - Alexia Gaudeul; Magdalena C. Kaczmarek (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
Recent evidence suggests that nudges, i.e. alterations in the decisional context, can have large effects on decisions and can improve individual and public welfare. This paper presents the results of a controlled experiment that was designed to evaluate not only the effectiveness of a default manipulation on decision making in a charity giving context, but also whether yielding or opposing a nudge affects attitudes, and whether nudging intentions (pledges) translate into behaviour (donations). The results show that while making pledges the default increased pledges, it did not increase donations because the nudge affected only participants who were close to indifference between pledging and not pledging and were thus unlikely to actually do the effort of translating their pledges into donations. Participants who were nudged to pledge pledged more often than participants who were nudged to keep, but they were less likely to maintain their participation in the experiment, and those who kept participating were less likely to pledge again. This, along with high attrition among nudged pledgers explains why nudging pledges did not result in higher actual donations. We interpret our findings in terms of a selection effect of nudges, and discuss practical implications of our experiment in terms of the applicability of default-based nudges as a tool for policy interventions.
Keywords: C9; D04; D10; D64; H41; 330; attitudes; decision making; charity giving; defaults; intentions; nudges; pro-social behaviour; selection effect